Effect of weight loss on pregnancy outcomes, neuronal-reproductive-metabolic hormones and gene expression profiles in granulosa cells in obese infertile PCOS patients undergoing IVF-ET - Wu, Limin; Fang, Qunying; Wang, Mengli; Wang, Yurui; Zhu, Xinyi; Fang, Zhaohui; Lu, Fangting; Xu, Bo; Jin, Rentao; Han, Hui; Tong, Xianhong (Frontiers in Endocrinology, 2022)
OBJECTIVE: To investigate the effect of weight loss on pregnancy outcomes, PCOS related neuronal-reproductive-metabolic hormones and ovarian granulosa cell gene expression profiles in obese PCOS infertile patients undergoing IVF-ET. METHODS: 75 patients undergoing IVF-ET due to tubal factors alone collected as control group (group A), and 352 patients with obese PCOS infertility were divided into four groups according to the amount of weight loss before IVF: 0 kg (group B), 1-5 kg (group C), 5-10 kg (group D), and >10 kg (group E). Six cases of ovarian granulosa cells were collected randomly with the random number table method in each group for detecting mRNA profiling. Pathway networks and biological functions of the differentially expressed genes were analyzed. Validation by RT-PCR was performed. RESULTS: (1) The levels of luteinizing hormone(LH) , testosterone(T) and homeostasis model assessment insulin resistance(HOMA-IR) in group E were significantly lower than those in groups B and C (P<0.05). (2) Compared with groups A and E, groups B and C showed increased total gonadotropin (Gn) and days of Gn stimulation (P<0.05), and the level on hCG day and number of oocytes obtained in group B was significantly less than that in group E (P<0.05 or 0.01). Embryo implantation rate, clinical pregnancy rate and live birth rate were increased and miscarriage rate was decreased in groups A, D and E compared with group B (P<0.05 or 0.01). (3) There are down and up-regulation of genes that are involved in neuronal-reproductive-metabolic endocrine, transcriptional regulation, cell proliferation and differentiation,etc. RNA-Seq results were validated by real time PCR analysis for the expression of FSHR, Smad7 and GPX3 genes that are known to have an important role in follicular development. Functional alterations were confirmed by the improvement in the ovarian responsiveness to Gn and embryo quality. Conclusion: Weight loss more than 5kg may regulate the neuroreproductive endocrine hormone secretion, insulin resistance and gene expression profiles of ovarian granulosa cells, so as to improve the ovarian responsiveness to Gn, the embryo quality, embryo implantation rate, clinical pregnancy rate, live birth rate, and reduce the spontaneous abortion rate in obese infertile PCOS patients undergoing IVF-ET.